2012
DOI: 10.1073/pnas.1207036109
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic assembly of heterochromatin in Drosophila melanogaster triggered by transposable elements

Abstract: A persistent question in biology is how cis-acting sequence elements influence trans-acting factors and the local chromatin environment to modulate gene expression. We reported previously that the DNA transposon 1360 can enhance silencing of a reporter in a heterochromatic domain of Drosophila melanogaster. We have now generated a collection of variegating phiC31 landingpad insertion lines containing 1360 and a heat-shock protein 70 (hsp70)-driven white reporter to explore the mechanism of 1360-sensitive silen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
106
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 43 publications
6
106
0
Order By: Relevance
“…Similarly, in Drosophila, two distinct RNAi-like processes for silencing Tns have been elucidated. In the germline, the Piwi-interacting RNA (piRNA) pathway generates small RNAs that suppress Tns by inducing heterochromatin formation (Vagin et al 2006;Aravin et al 2007;Brennecke et al 2007;Sentmanat and Elgin 2012;Le Thomas et al 2013). In somatic cells, esiRNAs silence retroTns via a Dicer 2 (Dcr-2)/Argonaute 2 (Ago2)-dependent mechanism (Chung et al 2008;Czech et al 2008;Ghildiyal et al 2008;Saito and Siomi 2010;Xie et al 2013).…”
mentioning
confidence: 99%
“…Similarly, in Drosophila, two distinct RNAi-like processes for silencing Tns have been elucidated. In the germline, the Piwi-interacting RNA (piRNA) pathway generates small RNAs that suppress Tns by inducing heterochromatin formation (Vagin et al 2006;Aravin et al 2007;Brennecke et al 2007;Sentmanat and Elgin 2012;Le Thomas et al 2013). In somatic cells, esiRNAs silence retroTns via a Dicer 2 (Dcr-2)/Argonaute 2 (Ago2)-dependent mechanism (Chung et al 2008;Czech et al 2008;Ghildiyal et al 2008;Saito and Siomi 2010;Xie et al 2013).…”
mentioning
confidence: 99%
“…Most piRNA sequences in the Drosophila genome map to heterochromatic regions (Saito et al 2006), and several lines of investigation have demonstrated that Piwi and HP1a can physically interact (Brower-Toland et al 2007;Mendez et al 2011). Moreover, transcriptional silencing of retrotransposons by the Piwi-piRNA system involves recruitment of HP1a to transposable elements (Wang and Elgin 2011;Sentmanat and Elgin 2012;Huang et al 2013). Piwi also participates in activities that are not directly related to transposon silencing.…”
mentioning
confidence: 99%
“…A careful examination of this domain revealed a correlation between the presence of the repetitive element 1360 and the variegating phenotype (Sun et al 2004). Follow-up studies found that incorporating 1360 sequences into the hsp70-white transgene construct could increase the gene silencing observed at a subset of insertion sites (Haynes et al 2006;Sentmanat and Elgin 2012). However, these studies also showed that the presence of 1360 was not sufficient to induce PEV-and heterochromatin formation-in general, as full expression, rather than variegation, is observed for insertions of the 1360-hsp70-white transgene at most sites in the euchromatic chromosome arms (Haynes et al 2006;Sentmanat and Elgin 2012).…”
mentioning
confidence: 99%
“…Follow-up studies found that incorporating 1360 sequences into the hsp70-white transgene construct could increase the gene silencing observed at a subset of insertion sites (Haynes et al 2006;Sentmanat and Elgin 2012). However, these studies also showed that the presence of 1360 was not sufficient to induce PEV-and heterochromatin formation-in general, as full expression, rather than variegation, is observed for insertions of the 1360-hsp70-white transgene at most sites in the euchromatic chromosome arms (Haynes et al 2006;Sentmanat and Elgin 2012).The available data suggest that PEV is caused by spreading of adjacent heterochromatin to encompass the reporter gene (Weiler and Wakimoto 1995;Vogel et al 2009). The effectiveness of this spreading is thought to be stochastic, thus leading to the variegating phenotype.…”
mentioning
confidence: 99%
See 1 more Smart Citation